On the occurrence of green mosaic disease on mulberry in India - GUPTA, V.P. (Indian Phytopathology, 2002)
A disease of mulberries, with green mosaic symptoms, was observed on leaves of a Japanese variety, Kairyorosa, grown in the Central Sericulture Research and Training Institute, India. Studies were carried out on the causative agent and the transmission of the disease. On establishment of grafts and new growth, 72.2% of 18 buds on diseased stocks showed typical symptoms, whereas all shoots from cuttings of diseased plants exhibited symptoms. Mechanical inoculation did not transmit the disease. An antibiotic treatment did not inhibit symptom development, suggesting that the causative agent was a virus and not a phytoplasma. It is suggested that the virus may be a new record on mulberry and it may have an insect vector.